The dynamics of the authority to investigate banking crimes - Agung Prayana; Slamet Suhartono; Yovita Arie Mangesti (Technium Social Sciences Journal, 2024)
Banking crimes, not only disrupt the stability of country’s economy, and violate the human rights of Bank customers, to live free from fear guaranteed by Article 28G paragraph (1) of the 1945 Constitution of the Republic of Indonesia, which is formulated: "Every person shall have the right to protection of his/her person, family, honor, dignity, and property under his/her control, and shall have the right to security and protection from the threat of fear to do or not to do something which is a human right". In addition, the Banking crime is also contrary to the value of justice that should be realized through positive law and its law enforcement.